2018
DOI: 10.16986/huje.2018038796
|View full text |Cite
|
Sign up to set email alerts
|

Conversation Analysis in Language Teacher Education: An Approach for Reflection Through Action Research

Abstract: This paper outlines a practical approach for professional language teachers in secondary and adultlearning contexts to enhance their reflective teaching practices through conversation analysis-based action research. Conversation analysis (CA) can provide English as a foreign or second language (EFL/ESL) teachers with insights into not only classroom-discourse dynamics but also the language-learning processes of their learners. As exposure to CA becomes increasingly common in language teacher education programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…As Takeda (2013) found that conducting CA will be beneficial for English language teachers to understand their students and interactional issues in the classroom. His finding was supported by Hale et al (2018) who found that CA can provide teachers with a powerful analytic lens to view language use in their classrooms-both their own language use, and that of their students-in order to make pedagogical changes that can enhance learning.…”
Section: Introductionmentioning
confidence: 94%
“…As Takeda (2013) found that conducting CA will be beneficial for English language teachers to understand their students and interactional issues in the classroom. His finding was supported by Hale et al (2018) who found that CA can provide teachers with a powerful analytic lens to view language use in their classrooms-both their own language use, and that of their students-in order to make pedagogical changes that can enhance learning.…”
Section: Introductionmentioning
confidence: 94%
“…Most researches on the theme of CA in classroom discourse were done in language learning classrooms especially in second-language and foreign-language classrooms, like the studies mentioned above (Hale et al, 2018). However, with too many researches regarding SLA, they are criticised to be narrowly focusing on grammatical competence (Sidnell & Stivers, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reflexive practices have enjoyed wide acceptance in language teaching and education for quite some time and have been institutionalized at different levels to varying degrees of success. As Hale, Nanni, and Hooper (2018) and Ghafarpour (2017) have shown, close analyses of the way we talk and interact offer us detailed insights into our practices as teachers and educators and thus can initiate reflection and, if necessary, change. Here, reflection was initiated by the analysis of data that stem from a two-day workshop for German L2 researchers and university educators in West Africa.…”
Section: Discourse Analysis As a Starting Point For Reflexive Practicementioning
confidence: 99%